Competitive Cell Death Interactions in Pulmonary Infection: Host Modulation Versus Pathogen Manipulation - FitzGerald, Ethan S.; Luz, Nivea F.; Jamieson, Amanda M. (Frontiers in Immunology, 2020)
In the context of pulmonary infection, both hosts and pathogens have evolved a multitude of mechanisms to regulate the process of host cell death. The host aims to rapidly induce an inflammatory response at the site of infection, promote pathogen clearance, quickly resolve inflammation, and return to tissue homeostasis. The appropriate modulation of cell death in respiratory epithelial cells and pulmonary immune cells is central in the execution of all these processes. Cell death can be either inflammatory or anti-inflammatory depending on regulated cell death modality triggered and the infection context. In addition, diverse bacterial pathogens have evolved many means to manipulate host cell death to increase bacterial survival and spread. The multitude of ways that hosts and bacteria engage in a molecular tug of war to modulate cell death dynamics during infection emphasizes its relevance in host responses and pathogen virulence at the host pathogen interface. This narrative review outlines several current lines of research characterizing bacterial pathogen manipulation of host cell death pathways in the lung. We postulate that understanding these interactions and the dynamics of intracellular and extracellular bacteria regulated cell death manipulation, may lead to novel therapeutic approaches for the treatment of intractable respiratory infections.